Bagasse: A Potential Organic Soil Amendment Used in Sugarcane Production: SL477/SS690, 8/2020 - Bhadha, Jehangir H.; Xu, Nan; Khatiwada, Raju; Swanson, Stewart; LaBorde, Chris (EDIS, 2020)
Bagasse is an agricultural by-product derived from the sugarcane milling process. It is a dry and fibrous residue left after the extraction of sugar juice from sugarcane. Over 2 million metric tons of bagasse is generated each year in South Florida, and need exists to find environmentally sustainable, yet economically viable use for it. Application of bagasse as a potential soil amendment on mineral soils to grow sugarcane seems like a good option to utilize the product. This factsheet explores the feasibilty of using bagasse as a organic soil amendment to grow sugarcane on mineral soils in South Florida.